Research on the problems and Countermeasures in the safety supervision of dangerous chemicals in Qingyang City. Issue 3 (May 2020) - Sun, Ning; Gai, Ke; Wang, Yipeng; Li, Zhenhua; Chen, Zhanjun
Abstract: This paper mainly analyses the problems existing in the safety supervision of dangerous chemicals in Qingyang City, and further provides scientific and reasonable countermeasures for the existing problems, so as to effectively prevent and reduce the accidents of dangerous chemicals and ensure that people's lives and properties are not threatened.